Prevalence and clinical profile of microcephaly in South America pre-Zika, 2005-14: prevalence and case-control study - Orioli, Iêda M. (2017)
Objective To describe the prevalence and clinical spectrum of microcephaly in South America for the period 2005-14, before the start of the Zika epidemic in 2015, as a baseline for future surveillance as the Zika epidemic spreads and as other infectious causes may emerge in future.Design Prevalence and case-control study.Data sources ECLAMC (Latin American Collaborative Study of Congenital Malformations) database derived from 107 hospitals in 10 South American countries, 2005 to 2014. Data on microcephaly cases, four non-malformed controls per case, and all hospital births (all births for hospital based prevalence, resident within municipality for population based prevalence). For 2010-14, head circumference data were available and compared with Intergrowth charts.Results 552 microcephaly cases were registered, giving a hospital based prevalence of 4.4 (95% confidence interval 4.1 to 4.9) per 10 000 births and a population based prevalence of 3.0 (2.7 to 3.4) per 10 000. Prevalence varied significantly between countries and between regions and hospitals within countries. Thirty two per cent (n=175) of cases were prenatally diagnosed; 29% (n=159) were perinatal deaths. Twenty three per cent (n=128) were associated with a diagnosed genetic syndrome, 34% (n=189) polymalformed without a syndrome diagnosis, 12% (n=65) with associated neural malformations, and 26% (n=145) microcephaly only. In addition, 3.8% (n=21) had a STORCH (syphilis, toxoplasmosis, other including HIV, rubella, cytomegalovirus, and herpes simplex) infection diagnosis and 2.0% (n=11) had consanguineous parents. Head circumference measurements available for 184/235 cases in 2010-14 showed 45% (n=82) more than 3 SD below the mean, 24% (n=44) between 3 SD and 2 SD below the mean, and 32% (n=58) larger than -2 SD.Conclusion Extrapolated to the nearly 7 million annual births in South America, an estimated 2000-2500 microcephaly cases were diagnosed among births each year before the Zika epidemic began in 2015. Clinicians are using more than simple metrics to make microcephaly diagnoses. Endemic infections are important enduring causes of microcephaly.